An innovative continuing medical education approach of general practitioners on vaccination: ForMéVac. (13th November 2019) - Guagliardo, C; Cortaredona, S; Banide, M C; Burlot, E; Bouvenot, J; Jozancy, F; Verger, P
Abstract: Background: General practitioners (GPs) play a central role in vaccinating the population in France. In a context of mistrust regarding vaccination, and because patients increasingly question their GP about vaccines, we designed the continuing medical education (CME) module in order to 1) reinforce GPs knowledge about vaccination 2) help GPs answer questions most frequently asked by their patients and 3) evaluate the impact of this module on their vaccine prescriptions. Methods: The CME module lasted 3 hours and focused on MMR, meningitis C and seasonal influenza vaccines; GPs were given confidential feedback information on percentages of their patients vaccinated. We included GPs practicing in Southeastern France and with less than 60% of their child patients (aged between 10 and 34 months) with 2 reimbursements of MMR vaccines (data obtained from the Health Insurance Fund). Eligible GPs were then randomly assigned to three groups: those offered either a face-to-face or e-learning CME module and a control group without CME. We used vaccine reimbursement rates for MMR 2-doses, Meningitis C, seasonal influenza as proxies for vaccine prescription rates, and a difference in differences approach to compare reimbursement rates in the year before the CME session and in the 24 months post-intervention. Results: Compared to the control group, vaccine reimbursement rates for 2-dose MMR and meningitis C increased by 6% and 4% respectively (p < 0.05) among patients of GPs who participated in the face-to-face CME session (52 GPs, with 1 842 children). For seasonal influenza vaccine, we found a 12% increase in the face-to-face group (p < 0.01). We found no statistically significant increase in the e-learning group (19 GPs, with 674 children) whatever the vaccine. Conclusions: We found a modest impact of face-to-face CME session with feedback on GPs practices for childhood vaccines and a stronger one for seasonal influenza. Key messages: The very positive feedback from face-to-face training highlights the fact that this type of training, which bring knowledge on vaccination in general and specific vaccines to GPs, is necessary. We found weak evidence for efficiency of CME sessions associated with audit/feedback to modify GPs practices regarding MMR and meningitis C vaccines.